EFFECT OF COMBINING LEUCAENA AND INDIGOFERA LEAVES IN SWAMP GRASS-BASED DIETS ON DIGESTIBILITY, RUMEN FERMENTABILITY AND METHANOGENESIS - Riswandi; A. I. M. Ali; Muhakka (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research was conducted to evaluate the effect of the combination of Leucaena and Indigofera in swamp grass-based rations on the quality or quantity of feed produced. The research was carried out based on a completely randomized design (CRD) consisting of four treatments and four replications. The types of forage used include termite Bento grass (Leersia hexandra) from swamp land; legumes Leucaena and Indigofera. The treatments consisted of A = swamp grass and concentrate (70%:30%), B = swamp grass, Leucaena and concentrate (40%:30%:30%), C = swamp grass, Indigofera and concentrate (40%:30%:30%), D = swamp grass, Leucaena, Indigofera and concentrate (40%:15%:15%:30%). The observed variables consisted of dry matter digestibility (DMD), pH, total Volatile Fatty Acid (TVFA), N-ammonia (N-NH3), partial VFA, methane gas, total bacteria and protozoa. The study showed that the combination of tree legumes increased (P<0.05) the digestibility values of DM, TVFA, propionic acid, butyrate and total bacteria, while the levels of N-NH3, acetic acid, acetate-propionate ratio, methane gas, methane gas production and protozoa decreased (P<0.05). Based on the results of the study, it can be concluded that the combination of tree legumes in the ration can increase digestibility, improve rumen fermentation characteristics and reduce methane gas production.